2002
DOI: 10.1159/000063074
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Urinary Trypsin Inhibitor (UTI) on Hepatic Microvasculature in Hypotensive Brain-Dead Rats

Abstract: Background/Aims: We examined the protective effects of a protease inhibitor, urinary trypsin inhibitor (UTI), on livers of brain dead rats associated with systemic hemodynamic instability. Methods: Brain death was induced by inflating a balloon catheter placed in the epidural space in rats followed by intravenous administration of UTI for 6 h. The hemodynamic, functional and morphological changes in the liver were examined. Results: The induction of brain death resulted in a significant decrease in both mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…27,28 Protease inhibitors such as urinary trypsin inhibitor decreased leukocyte recruitment and release of cytokines and proved its ability to restore hepatic tissue flow in the liver of hypotensive BD rats. 32 Another strategy is based on the cytoprotective and antioxidative properties of stress proteins such as metalloprotoporphyrin cobalt protoporphyrin, an inducer of HO-1. 30 In our present study, we performed donor therapy with methylprednisolone since this option offers the advantage of counteracting immunologic and also hormonal alterations caused by BD.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Protease inhibitors such as urinary trypsin inhibitor decreased leukocyte recruitment and release of cytokines and proved its ability to restore hepatic tissue flow in the liver of hypotensive BD rats. 32 Another strategy is based on the cytoprotective and antioxidative properties of stress proteins such as metalloprotoporphyrin cobalt protoporphyrin, an inducer of HO-1. 30 In our present study, we performed donor therapy with methylprednisolone since this option offers the advantage of counteracting immunologic and also hormonal alterations caused by BD.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in animal models have previously demonstrated the relation between brain death and the rapid infiltration of leukocyte populations in peripheral organs with intense upregulation of their associated products 14 . Concordantly, human studies have suggested that brain death of potential organ donors induces an inflammatory response mediated by IL-1b, IL-6, TNF alpha, CXCL1, CCL2, CCL5 [39][40][41] that could affect graft quality and function 42,43 . Although our study is not without limitations, it has generated valuable indications.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that BD enhances the expression of P-selectin (13). and ICAM-1 in the liver (13-15), kidney (9), and lungs (16). The data presented here demonstrated that the expression of P-selectin on mesenteric microvessels increased at 30 min with no further increase at the 180-min time point.…”
Section: Discussionmentioning
confidence: 99%